Intrathecal administration of anti-HER2 treatment for the treatment of meningeal carcinomatosis in breast cancer: A metanalysis with meta-regression. (August 2020) - Zagouri, Flora; Zoumpourlis, Panagiotis; Le Rhun, Emilie; Bartsch, Rupert; Zografos, Eleni; Apostolidou, Kleoniki; Dimopoulos, Meletios-Athanasios; Preusser, Matthias
Highlights: Intrathecal anti-HER2 is a promising treatment option in HER2 positive BC leptomeningeal metastases. Median overall survival in patients treated with intrathecal trastuzumab 5.7 months. Tolerable safety profile; no serious adverse events in 90% of cases. Abstract: Leptomeningeal Metastases (LM) is a turning point in terms of prognosis and quality of life of patients with breast cancer (BC). Intrathecal therapy is largely used for the treatment of breast cancer LM. In this metanalysis with meta -regression, we gathered data on intrathecal (IT) trastuzumab administration in patients with HER2 positive breast cancer with LM. A total of 24 articles (58 patients) were included in the study and intrathecal trastuzumab was used in all patients. The mean age at IT administration was 50.7 years (SD 11.4, range 24–80) and the mean total dose of IT trastuzumab was 711.9 mg (SD 634.9, median 450). IT trastuzumab was used both alone (n = 20) and in combination with systemic pharmacotherapy (n = 37). No serious adverse events were reported in 87.9% of cases. In this selected population a significant clinical improvement was observed in 55.0% of cases while stabilization was reported in 14% of cases. CSF response was observed in 55.6% of the cases. MRI was improved or stable in 70.8% of the cases. Interestingly, the CNS-PFS was 5.2 months and the median OS was 13.2 months. A clinical improvement (HR 0.13, 95% CI 0.03–0.49) and CSF response (HR 0.13, 95% CI 0.03–0.58) were associated with a longer CNS-PFS. The association of longer CNS-PFS with radio- or neurosurgery prior to the administration of IT trastuzumab did not reach statistical significance. This metanalysis with meta -regression indicates that IT trastuzumab in patients with HER2 positive breast cancer LM might be a safe and effective treatment, but further prospective studies are needed to definitively prove such a point.